DIVORCE SETTLEMENT DUE TO HOME VIOLENCE DURING THE PANDEMIC COVID 19 IN MEDAN CITY - Erniyanti; Mukidi Mukidi; Syahrul Bakti Harahap; Nelvitia Purba (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
This article aims to examine the procedure for resolving divorce caused by domestic violence during the Covid-19 pandemic in Medan City. Since the end of 2019, a deadly virus emerged from the Covid-19 pandemic, which is one of the strategies of Indonesian government in suppressing the spread. Covid -19, which continues to increase, establishes a Large-Scale Social Restriction policy which causes people to do more activities at home, both for studying, working, and even layoffs occur everywhere so that the community's economy is disrupted. At this time divorce cases in Indonesia in general and in particular in Medan City continue to increase in number until mid-2020 increase ranges from 15-20 percent. The consequences of the Covid 19 Pandemic greatly affect all aspects of human life in the world related to economy and behavior due to the pressure of life and this domestic violence occurred. The process of resolving domestic violence cases through the penal channel at investigation level is a number of activities carried out by law enforcement officials, namely: investigations, investigations, coercive measures and the making of an official report. The reason for law enforcement officials to carry out these activities is because a criminal act has occurred (a criminal act). For victims of domestic violence after processing in a criminal court, the discomfort resulting from this domestic violence process is submitted to a religious court. In the process, the judge has an obligation to reconcile a married couple who are about to divorce, this is based on Law Number 1 of 1974 concerning Marriage Article 39 jo. PP. Number 9 of 1975 concerning the implementation of Law Number 1 of 1974 17 Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2008 concerning Mediation Procedures in Courts concerning Marriage Article 31 jo. Law Number 7 of 1989 concerning Religious Courts Articles 65 and 82. The decision for divorce will be handed down by the panel of judges if efforts to conciliate are truly unsuccessful.